Islamic Moderation in Salaf based Education at the ad-Dimyati Lalang Islamic Boarding School, Wonojati, Jenggawah, Jember Regency - Rusdiyanto , Rusdiyanto; Werdiningsih , Indah; Mufaizin, Mufaizin (Al-Insyiroh: Jurnal Studi Keislaman, 2022)
Islamic moderation is more popular or known as moderate Islam. The emergence of the word ‘moderate’ Islam by its pioneers is due to the existence of extremist Islam, so Islamic moderation can be a solution that is seen as not excessive or extreme. The objectives of this research are, firstly, planting Islamic moderation in education at Salaf Islamic Boarding Schools. Second, planting Islamic moderation in culture at Salaf Islamic Boarding Schools outside the classroom. The results of the research include, firstly, cultivating Islamic moderation in education at Salaf Islamic Boarding Schools. In learning, students are provided with special and general knowledge. A santri at least understands and understands science, especially during his stay at the boarding school and also general sciences while taking part in pesantren-based moderation in learning in later life. Special knowledge such as interpretation, nahwu, balaghah and other yellow books as the basic knowledge of Islamic boarding schools. While general science. For example, about tolerance as an understanding when entering the community so that it is easy to socialize and protect the general public. Second, cultivation of Islamic Moderation in culture at Salaf Islamic Boarding Schools outside the classroom through the kiai figure as the leader of the pesantren, the character and success of the pesantren is very dependent on knowledge, charisma and authority, as well as the skills of its Kyai